Assessment of a modified release verapamil.HCl matrix compacts : Effect of formulation composition on the in-vitro release kinetic (2013)
ABSTRACT: Verapamil hydrochloride is a drug used to treat arrhythmias. In this study, a D-optimal mixture design with 16 runs was used to select the best combination of three polymers into a matrix that rendered an 8 h in vitro release profile of verapamil. hydrochloride (HCl) which fulfill a once-a-day modified release in compliance with the United States Pharmacopeia (USP) specifications. The Korsmeyer-Peppas model was used to fit the dissolution data since it presented the best fitting characteristics. A cubic model predicted the best formulation of verapamil.HCl containing carnauba wax, hydroxypropyl methyl cellulose and Avicel_PH101 at the 40, 20 and 40% levels, respectively. Validation runs confirmed the accuracy of the cubic models which include these three components.